2013
DOI: 10.1038/ncomms2587
|View full text |Cite
|
Sign up to set email alerts
|

Moderate doping leads to high performance of semiconductor/insulator polymer blend transistors

Abstract: Polymer transistors are being intensively developed for next-generation flexible electronics. Blends comprising a small amount of semiconducting polymer mixed into an insulating polymer matrix have simultaneously shown superior performance and environmental stability in organic field-effect transistors compared with the neat semiconductor. Here we show that such blends actually perform very poorly in the undoped state, and that mobility and on/off ratio are improved dramatically upon moderate doping. Structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
305
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(315 citation statements)
references
References 49 publications
8
305
2
Order By: Relevance
“…Blends of an organic semiconductor and insulating polymer have been successfully employed for a range of opto‐electronic devices including field‐effect transistors (FETs)5, 6, 7, 8, 9, 10, 11, 12 and bulk‐heterojunction solar cells,13, 14 as well as applications such as elastic conductors15, 16, 17 and organic thermoelectrics 18, 19. In order to maintain a good device performance at low content of the conjugated polymer judiciously chosen processing schemes are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Blends of an organic semiconductor and insulating polymer have been successfully employed for a range of opto‐electronic devices including field‐effect transistors (FETs)5, 6, 7, 8, 9, 10, 11, 12 and bulk‐heterojunction solar cells,13, 14 as well as applications such as elastic conductors15, 16, 17 and organic thermoelectrics 18, 19. In order to maintain a good device performance at low content of the conjugated polymer judiciously chosen processing schemes are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…R ecently, a wide range of new applications for doped polymers has emerged, which include thermoelectrics 1,2 , spintronics 3 , (opto)electronics 4 and biosensors 5 . This recent progress was mainly driven by the design of robust molecular dopants 6 , which when mixed with the semiconductor in controlled amounts can finely tune the electrical characteristics of the material.…”
mentioning
confidence: 99%
“…Although the P3HT:TSS transistor exhibited a field-effect mobility on the order of B10 À 2 cm 2 V À 1 s À 1 but a reduced on/off ratio (B10 3 ) with the threshold voltage shifting towards positive values, the P3HT:PSS transistor exhibited a high fieldeffect mobility (B10 À 1 cm 2 V À 1 s À 1 ) and a high on-off ratio (B10 6 ) without any threshold shift. This result implied that the light doping process on P3HT would help to extend the electrical connectivity and minimize the trap sites, leading to highperformance electronics 41 . We further noted that the P3HT:TSS film did not exhibit the TMC nanomorphology or the interconnected network that were clearly observed in the P3HT:PSS film, suggesting that the molecular dopant could not serve as a template for the structural orientation (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, we observed that the P3HT:PSS film was lightly doped to have a charge-carrier density of 4.6 Â 10 16 cm À 3 , whereas the P3HT:TSS film was moderately doped to have a charge-carrier density of 2.2 Â 10 17 cm À 3 , which is an order of magnitude higher than that of the P3HT film. This behaviour might be interpreted as suggesting the possibility of a light and moderate doping effect on the corresponding transistor performances [39][40][41] . To verify the doping effect on the transistor performance, the transfer characteristics with a bottom-gate and top-contact transistor configuration (L ¼ 50 mm, W ¼ 1,000 mm) for the corresponding films were determined as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation